Ambiguity attitudes: An experimental investigation - Gary Charness; Edi Karni; Dan Levin (The Johns Hopkins University, Department of Economics, 2012)
This paper reports the results of experiments designed to test (a) whether and to what extent individuals display non-neutral ambiguity attitudes in their choice behavior and (b) if and how do ambiguity attitudes change as a result of interpersonal interactions and persuasion. To address the first question we designed and conducted experiments involving individual choice between betting on ambiguous and unambiguous events of their choice. We found that a large majority of subjects display ambiguity-neutral attitudes, many others display ambiguity-incoherent attitudes, and few subjects display either ambiguity-averse attitudes or ambiguity-seeking attitudes. To address the second question we introduced a new experimental design with a built-in incentive to persuade. We found that interpersonal interactions without incentive to persuade have no effect on behavior, but when incentives were introduced, the ambiguity-neutral subjects were better able to persuade ambiguity seeking and ambiguity-incoherent subjects to follow ambiguity-neutral choice behavior. No such influence was detected with respect to ambiguity-neutral subjects.
Keywords: 330